Evaluasi Spesifikasi Produk Relay di PT Schneider Electric Manufacturing Batam - Andreas Dwi Susilo; Debora Anne Yang Aysia (Jurnal Titra, 2015)
Relay is one of several products that is produced by PT. Schneider Electric Manufacturing Batam. The biggest reject in relay is operating voltage reject (5.18%). Relay’s operating voltage is related to the movement of armature to ferrite core, and moving terminal to fixed terminal. The movement is measured undirrectly by four characteristics in relay product. They are flatness, height, length, and allignment. The problem is operating voltage reject is still occured in relay product eventhough the four characteristics are within specification limit. Those characteristic are analyzed with linear regression in order to know the correlation between each characteristic with operating voltage. There are only three characteristics that have correlation with operating voltage. New spesification limit for each characteristic which is correlated with operating voltage is searched. Wilcoxon test is used as a tools to find the new spesification limit. The final result is operating voltage can be decreased by 4.88%.